P2.042 An Audit of HIV Testing Rates in Patients Admitted with Pneumonia Pre- and Post- Implementation of Opt-Out HIV Testing For Acute Medical Admissions. (13th July 2013) - Wallis, E; Saunders, J; Orkin, C
Abstract : Background: UK National Guidelines for HIV Testing recommend that an HIV test should be considered in all general medical admissions where diagnosed HIV prevalence in the local population exceeds two in 1000 population as well as for all patients presenting with certain indicator diseases. The aim of this audit was to determine if HIV testing rates of patients admitted with pneumonia improved after the implementation of opt-out testing for all acute medical admissions. Methods: HIV testing rates were compared for patients admitted with pneumonia before (September 2011) and after (September 2012) implementing opt-out testing for acute medical admissions. Patients were identified from hospital coding data for pneumonia during their inpatient stay. Electronic patient records were used to determine which patients had received a test for HIV during their admission. Results: Seventy-nine patients were admitted with pneumonia in September 2011 and 86 in September 2012. Before opt-out HIV testing, 4/79 (5.1%) patients were tested for HIV during their admission (mean age 63.5 years), with no positive tests. Following the implementation of opt-out testing, 22/86 (25%) patients admitted with pneumonia were tested for HIV (mean age 62.5 years), with no patients testing positive. Since implementing opt-out HIV testing for acute medical admissions the rate of HIV testing in patients admitted with pneumonia increased from 5.1% to 25% (p = 0.0002). Conclusion: Following the implementation of opt-out HIV testing for acute medical admissions, the rate of testing in patients with a diagnosis of pneumonia has significantly increased. However, despite national guidelines and regional opt-out testing for acute medical admissions, a test was only performed in a quarter of eligible patients. Further work needs to be done in all areas of the hospital to increase awareness of HIV testing and to ensure rates of testing continue to rise.